Considerations about jigsaw II cooperative learning technique in project-based learning among students of secondary education - Orcos, Lara; Curto Prieto, Marta (Nova Science Publishers, Inc., 2022)
The objective of this study is to know the impressions of a sample of students of the third course of Secondary Education (14-15 years old) who have used the Jigsaw II technique to work mathematical contents through project-based learning with contexts of everyday life. For this purpose, base groups and expert groups have been established from each content block, arithmetics, measurement, geometry, statistics and probability. The results obtained have been satisfying and represent a starting point for interdisciplinary collaborative work in the mathematics classrooms. © 2020 Nova Science Publishers, Inc.
Es un capítulo del libro: L. Orcos and M. Curto (2020), "Didactics of Mathematics: New Trends and Experiences": Considerations about Jigsaw II Cooperative Learning Technique in Project-Based Learning among Students of Secondary Education.
Keywords: collaborative learning; jigsaw II technique; mathematics; project-based learning; secondary education; Scopus(2)